Fattening heifers for the summer or early fall market. - Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
The two preceding tests with heifer calves were conducted without the use of grass. Varying amounts of grain and protein supplement were fed with silage during the winter season and then a full feed of grain was used to finish the.se heifers for the summer or early fall market. With experimental pastures available, grass is being used to the fullest extent in developing a system of deferred feeding for fattening heifers.
Keywords: Beef; Heifers; Protein; Market